2015
DOI: 10.1007/s00464-015-4584-0
|View full text |Cite
|
Sign up to set email alerts
|

Skill acquisition and stress adaptations following laparoscopic surgery training and detraining in novice surgeons

Abstract: A 3-week LS training programme promoted stress-related adaptations likely to directly, or indirectly, support the acquisition of new surgical skills, and many outcomes were retained after a 4-week period without further LS training. These results have implications for medical training and education (e.g. distributed training for skill development and maintenance, stress resource and management training) and highlighted possible areas for new research (e.g. longitudinal stress and skill profiling).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…Given the complexity of laparoscopic surgical skills, it is essential to have a necessary amount of practice time to allow the learner to sufficiently perform the task. Previous work by Crewther et al 6 had novices practice set-sequences of intracorporeal suturing and knot tying for a baseline of 120 minutes. Taken together, when training novice surgeons a baseline of training of 90-120 minutes is recommended.…”
Section: Acquisition -Performance Metricsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the complexity of laparoscopic surgical skills, it is essential to have a necessary amount of practice time to allow the learner to sufficiently perform the task. Previous work by Crewther et al 6 had novices practice set-sequences of intracorporeal suturing and knot tying for a baseline of 120 minutes. Taken together, when training novice surgeons a baseline of training of 90-120 minutes is recommended.…”
Section: Acquisition -Performance Metricsmentioning
confidence: 99%
“…Regardless of the practice schedule for skill acquisition, prefrontal cortex activation is necessary in the early stages of learning motor skills especially for complex, attention-demanding tasks like surgical skills. [29][30][31][32][33]38 Other investigations of surgical techniques have used a single task, e.g., knot tying, 8 endoscopic suturing and knot-tying, 9 laparoscopic intracorporeal suturing and knot-tying in a set sequence 6 and a laparoscopic suturing drill, 14 Lage 32 reported that the RDLPFC showed increased activation for RA practice at the end of acquisition as well as demonstrating increased DLPFC activation across acquisition. Our results for the simulated laparoscopic surgical tasks in acquisition show mixed results to those reported by Lage.…”
Section: Acquisition -Changes In Cortical Hemodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that skills need to be re-acquired each time the need arises. For example, trained human surgeons need to re-acquire their surgical proficiency after a period of absence (1), food-cashing mammals need to use manipulative skills to retrieve their stored food cashes after periods of hibernation (2), and songbirds need to re-develop high-quality songs to attract a mate after wintering or longdistance migration (3). Whereas learning novel motor skills is generally a lengthy process, the short-term availability of suitable mates and food items imposes a considerable time pressure on the re-acquisition of such specialized skills.…”
Section: Introductionmentioning
confidence: 99%